Analysis of the judgment from Fernández Ortega vs. México: gender, social class and ethnicity - Rodríguez Caguana, Adriana (2018)
This paper shall analyze the judgment from Fernández Ortega vs. México state by the Interamerican Court for Human Rights in August 2010. The study is carried from an integral perspective that includes factors of class, language, gender, and ethnicity that exist in the social anthropology. The Fernandez case involved a sexual rape that the victim had suffered by soldiers. The victim is an indigenous woman from the Tlapaneco/Me'phaa people. This case is very important for the jurisprudence of the Interamerican Court for Human Rights. We presume, however that the Court did not understand the complex relationship between class, language, gender and ethnicity. Finally it favoured only gender perspective, sidelining all other items. Is the Gender Theory sufficient to explain sexual rape and the human rights of indigenous women?